2010
DOI: 10.1080/03601234.2010.515504
|View full text |Cite
|
Sign up to set email alerts
|

Pesticide dissipation curves in peach, pear and tomato crops in Uruguay*

Abstract: Dissipation curves of azoxystrobin and of the neonicotinoids acetamiprid and thiacloprid in peach; azinphos-methyl and carbaryl in pear and azoxystrobin, chlorfenapyr and chlorpyrifos in high-tunnel tomato crops were studied in the Southern region of Uruguay. An analytical methodology based on solid phase extraction (SPE) and detection by High Performance Liquid Chromatography with Diode Array Detector (HPLC/DAD) was used for acetamiprid and thiacloprid. Coupled SPE and detection by Gas Chromatography with Mas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 8 publications
1
17
0
Order By: Relevance
“…However, as the PYR residues were well below the legal MRLs, longer evaluation times were not considered. Similar retention of residues without decline of the fungicide azoxystrobin on fruits stored in cold chambers were reported in tomato (Galietta et al, 2011). Moreover, cross-contamination with PYR has been detected when no appropriate clean up measures are taken.…”
Section: Pyr Degradation Curvessupporting
confidence: 63%
“…However, as the PYR residues were well below the legal MRLs, longer evaluation times were not considered. Similar retention of residues without decline of the fungicide azoxystrobin on fruits stored in cold chambers were reported in tomato (Galietta et al, 2011). Moreover, cross-contamination with PYR has been detected when no appropriate clean up measures are taken.…”
Section: Pyr Degradation Curvessupporting
confidence: 63%
“…Length of dietary exposure is a function of an insecticide's photolysis, hydrolysis, and oxidation rates. In field and greenhouse studies conducted with growing plants, beta‐cyfluthrin was found to have a half‐life of 1 to 2 d (Banerjee et al 2012), whereas chlorpyrifos, imidacloprid, and thiamethoxam had half‐lives of 2 to 6 d (Galietta et al 2011; Hassanzadeh et al 2012; Rahman et al 2015). Chlorantraniliprole has a reported half‐life of 16 to 17 d (Szpyrka et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Chlorfenapyr is a GC amenable pesticide and has been determined using GC equipped with ECD (Ditya et al, 2010;Ou et al, 2006;Rahman et al, 2012) and MSD (Galietta et al, 2011). Chlorfenapyr molecular weight is 407.6 g/mol.…”
Section: Gcmsmentioning
confidence: 99%
“…These parameters should be studied and have to fall in the criteria range, unless justified. Although dissipation of chlorfenapyr was previously studied in peach (Galietta et al, 2011), pakchoi (Ou, Huang, Wang, & Fan, 2006), leek (Rahman et al, 2012), chili and cabbage (Ditya, Das, Sarkar, & Bhattacharyya, 2010) and in grapes and vines (Abdallah, Almaz, Arief, & Abd El-Aleem, 2014), it was not studied in okra or squash fruits.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation